Americanah - Adichie, Chimamanda Ngozi, 1977- (New York : Alfred A. Knopf, 2013)
This novel tells a story of love, race and identity centered around a young man and woman from Nigeria who face difficult choices and challenges in the countries they come to call home. A young woman from Nigeria leaves behind her home and her first love to start a new life in America, only to find her dreams are not all she expected. As teenagers in Lagos, Ifemelu and Obinze fall in love. Their Nigeria is under military dictatorship, and people are fleeing the country if they can. The self-assured Ifemelu departs for America. There she suffers defeats and triumphs, finds and loses relationships, all the while feeling the weight of something she never thought of back home: race. Obinze, the son of a professor hoped to join her, but post-9/11 America will not let him in, and he plunges into a dangerous undocumented life in London
Keywords: Immigrants -- Fiction; Refugees -- Fiction; Nigerians -- United States -- Fiction; Nigerians -- England -- Fiction; Nigeria -- Fiction; Fiction